Is Vitamin A Deficiency a Growing Concern? A Pan-India Retrospective Study of 15,000 Individuals - Kushawaha, Rajkumar; Kallathiyan, Kallathikumar; Iyer, Sandhya; Sinkar, Prachi (Asian Journal of Biological and Life Sciences, 2019)
Introduction:Vitamin A deficiency is a very huge clinical burden; both subclinical as well as clinical. In the Indian scenario, it also forms a major aspect of the broad micronutrient deficiency. Absence of symptoms does not rule out deficiency and that is what makes diagnosing sub-clinical deficiency of Vitamin A imperative.Methods:Data from a total of 15,116 specimens analyzed for serum Vitamin A levels were studied for this report. The cohort consists of all age-groups, from infants to old adults and includes 8,226 males and 6,890 females respectively. Serum Vitamin A levels were analyzed using the superior platform of Liquid Chromatography - Mass Spectrometry.Results:The clinical reference range for Vitamin A levels vary as per age, but to understand the prevalence of borderline low and high Vitamin A scenario among Indians, 1SD values of less than 387 ng/mL and > 748 ng/mL was considered for further analysis. The total frequency of borderline low was detected to be 9.8%, while that for high was 10.6%. Geographical distribution analysis identified significant number of cases to be from North India and certain Southern States wherein it is a public health issue and a concern needing action as well as regions wherein deficiency is likely to exist.Conclusion:Our study is one of the few to assess a huge cohort of over 15,000 samples and present a detailed pan-India picture of low Vitamin A levels.
Keywords: Deficiency; India; Liquid Chromatography Mass Spectrometry; Micronutrient; serum; Vitamin A